Revealing 3D magnetization of thin films with soft X-ray tomography: magnetic singularities and topological charges - A. Hierro-Rodriguez (Nature Portfolio, 2020)
Although magnetic tomography has been used in the past to determine the 3D magnetization of materials its application to thin films remains challenging. Here the authors reconstruct the magnetization of a thin film, enabling the measurement of topological charges of magnetic singularities.